Hubungan Kepuasaan Pasien Terhadap Niat Kunjungan Ulang Masyarakat Terhadap Pelayanan Rawat Inap di Rumah Sakit Bhayangkara Kediri Jawa Timur - Nugraheni, Reny; Astutik , Wahyu Sri (Fakultas Farmasi Universitas Tjut Nyak Dhien, 2025)
The degree to which hospital services are perfected to meet the needs of the public for health care that complies with professional service standards and service standards while taking into account the capabilities and limitations of the public and government and making reasonable, efficient, and effective use of all available resources to provide safe, satisfactory care that complies with legal ethics and norms. The outcome of interdependent relationships and dependencies between different parts or facets of the hospital as a system is the quality of hospital services. Finding out how satisfied the community was with hospital inpatient services was the aim of the study. The study design measures patient satisfaction with hospital quality control using quantitative analysis. The research was conducted in August-December 2022. The study population was 11,017 respondents. The community satisfaction survey sample is part of the population calculated based on The Open Epi Collection of Epidemiologic Calculators. The public satisfaction survey instrument is a questionnaire developed in the form of an application where satisfaction assessment is given by the sample by giving an asterisk to the components in the questionnaire. SPSS was used to examine the data. Confidentiality, relevant information, and scientific advancement are all applied in this study. The results of bivariate analysis with the chi square test, it can be seen that most respondents were satisfied with inpatient services at the hospital and made a return visit to the hospital when sick by 214 respondents (76.1%), while the fewest respondents were not satisfied with inpatient services at the hospital, but made a return visit to the hospital when sick by 1 respondent (0.4%). The resulting p value is 0.014, which means that there is a relationship between inpatient services and patient re-visits at the hospital. The resulting relationship strength (OR) value is 10.19, which means that respondents who are satisfied with hospital inpatient services will make a return visit when sick to the same hospital 10.19 times greater than respondents who are not satisfied with hospital inpatient services. The research conclusion is that hospital customer satisfaction will reflect the quality of service that exists from the start of the patient or customer entering the hospital environment to going home or leaving and waiting to return.